Are frequent users of social network sites good information evaluators? An investigation of adolescents' sourcing abilities (¿Son los usuarios frecuentes de las redes sociales evaluadores competentes? Un estudio de las habilidades de los adolescentes para identificar, evaluar y hacer uso de las fuentes). Issue 1 (2nd January 2020) - Macedo-Rouet, Mônica; Salmerón, Ladislao; Ros, Christine; Pérez, Ana; Stadtler, Marc; Rouet, Jean-François
ABSTRACT: This study investigates the relationship between teenagers' use of social networking sites (SNS) and their sourcing abilities. Sourcing is defined as students' ability (1) to discriminate reliable and unreliable links based on source characteristics, (2) to value source criteria as means to select information resources and (3) to select reliable texts based on source characteristics. One hundred and forty-six students ( M age = 14.7 years old) completed three sourcing tasks, a questionnaire on SNS use, as well as language and memory skills tests. We found that SNS frequency of use negatively predicted both participants' ability to select the most reliable source among two conflicting sources on the same topic and their ability to cite source features when justifying their choice. SNS frequency of use was unrelated to students' assessment of source criteria, but vocabulary level was positively related to performance in this task. We discuss various explanations for the observed relationship between teenagers' SNS communication and their critical appraisal of information sources, and we propose avenues for instructional interventions aimed at fostering information skills.